Answer:
Point B is (1, 2)
Explanation:
Let us revise the rule of the translations
- If the point (x, y) translated horizontally to the right by h units then its image is (x + h, y) ⇒ T (x, y) → (x + h, y)
- If the point (x, y) translated horizontally to the left by h units then its image is (x - h, y) ⇒ T (x, y) → (x - h, y)
- If the point (x, y) translated vertically up by k units then its image is (x, y + k)→ (x + h, y) ⇒ T (x, y) → (x, y + k)
- If the point (x, y) translated vertically down by k units then its image is (x, y - k) ⇒ T (x, y) → (x, y - k)
∵ Point A = (-2, 0)
∵ T (3, 2) → A = B
→ By using the 1st and 3rd rules above, A is translated 3 units right and 2
units up to get B
∴ T (x, y) → (x + 3, y + 2)
∵ A = (x, y)
∵ x = -2 and y = 0
∴ B = (-2 + 3, 0 + 2)
∴ B = (1, 2)
∴ Point B is (1, 2)